South-South development cooperation and the socio-spatial reconfiguration of Latin America-Caribbean regionalisms: university education in the Brazil-Venezuela ‘Special Border Regime’ - Muhr, Thomas (Edward Elgar, 2016)
This chapter approaches the changing geometries of Latin America–Caribbean regionalisms through the lens of South-South cooperation and the role of university education in the construction of a Brazil–Venezuela cross-border sub-region termed ‘Special Border Regime’. Within the general reintensification of South–South cooperation in the geographical area, I concentrate on the Brazil–Venezuela official development cooperation between 2003 and 2015 and the transformation of the Southern Common Market (MERCOSUR) in relation to the Bolivarian Alliance for the Peoples of Our America – Peoples’ Trade Agreement (ALBA-TCP), to argue that a South–South cooperation counter-space is being produced in which university education is sought to be re-established as a fundamental right and state responsibility.